PELAKSANAAN PENDAFTARAN TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 - Ni Nyoman Adi Astiti (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2017)
Implementation of Land Registry According to Government Regulation No. 24 of 1997, basically aims to provide legal certainty both the certainty of the subject and its object. But in the implementation there are still obstacles such as easurement and posted announcements by the measuring officers suddenly come other people who recognize. The far location of the object of the land resulted in the registration fee of land. Indicators become problematic implementation of land registration so that land registration has not been able to realize legal certainty in its implementation. Even the factors of non-implementation of land registration that protect the rights of the community above are exacerbated by the issuance of false certificates as well as double certificates.